2020
DOI: 10.1093/nar/gkz1206
|View full text |Cite
|
Sign up to set email alerts
|

Integrative network analysis identifies cell-specific trans regulators of m6A

Abstract: N6-methyladenosine (m6A) is a reversible and dynamic RNA modification in eukaryotes. However, how cells establish cell-specific m6A methylomes is still poorly understood. Here, we developed a computational framework to systematically identify cell-specific trans regulators of m6A through integrating gene expressions, binding targets and binding motifs of large number of RNA binding proteins (RBPs) with a co-methylation network constructed using large-scale m6A methylomes across diverse cell states. We applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 69 publications
6
95
0
Order By: Relevance
“…In mammals, approximately 0.1 to 0.6% of adenines undergo m 6 A modification, with an average of 3 to 5 methylated sites in each mRNA. Notably, m 6 A modifications can be deposited onto the transcripts in tissue-and cell-type-specific manners (An et al, 2020).…”
Section: Characteristics Of M 6 a Modification And Related Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, approximately 0.1 to 0.6% of adenines undergo m 6 A modification, with an average of 3 to 5 methylated sites in each mRNA. Notably, m 6 A modifications can be deposited onto the transcripts in tissue-and cell-type-specific manners (An et al, 2020).…”
Section: Characteristics Of M 6 a Modification And Related Enzymesmentioning
confidence: 99%
“…Notably, the m 6 A modification-related methylase can be regulated by various factors involved in transcriptional, posttranscriptional (miRNAs and lncRNAs), and translational (phosphorylation, ubiquitination, or SUMOylation modification) regulation ( Du et al, 2018 ; Schöller et al, 2018 ; Zhu et al, 2018 ). In addition, several m 6 A modification regulators, such as ZFP217, SMAD2/3, CEBPZ, TARBP2, and TRA2A, have been found to regulate m 6 A modification of mRNAs by recruiting or repelling MTC in a cell-type-specific manner ( Aguilo et al, 2015 ; Barbieri et al, 2017 ; Bertero et al, 2018 ; Fish et al, 2019 ; An et al, 2020 ). In addition, a recent study reported that H3K36me3 recruited METTL14 thus guiding m 6 A deposition on nascent transcripts ( Huang et al, 2019 ).…”
Section: Overview Of Rna M 6 a Modificationmentioning
confidence: 99%
“…Another transcriptional factor, CAATT-box-binding protein CEBPZ, was demonstrated to directly recruit METTL3 to chromatin [ 68 ]. A large-scale computational screening aimed at identifying RNA-binding proteins as cell-specific trans regulators of m 6 A, and validated experimentally that TRA2A and CAPRIN1 could interact with METTL3 [ 69 ]. Fish et al found that the RNA-binding protein TARBP2 recruits METTL3 and deposits m 6 A on the introns of the target mRNA, regulating RNA splicing and stability [ 70 ].…”
Section: Regulation Of Mettl3 Expression and M 6 Amentioning
confidence: 99%
“…A number of studies have focused on dissecting m6A’s functions in cell culture systems, where transcriptome-wide m6A profiles and expression patterns of the writers, erasers and readers were found to vary among cell types ( An et al, 2020 ; Delaunay and Frye, 2019 ; Roundtree et al, 2017 ). In recent years, models have been made to conditionally disrupt specific m6A writers, erasers or readers in mouse tissues ( Cheng et al, 2019 ; Geula et al, 2015 ; Hsu et al, 2017 ; Ivanova et al, 2017 ; Lee et al, 2019 ; Li et al, 2017 ; Li et al, 2018 ; Lin et al, 2017 ; Shi et al, 2018 ; Wu et al, 2018 ; Xu et al, 2017 ; Yoon et al, 2017 ; Zhang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%